PENERAPAN MODEL PEMBELAJARAN TEACHING WITH ANALOGIES MATERI TEKANAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS VIII SMP NEGERI 3 PEKANBARU - Asrimah Dwi Hardinah; Azhar Azhar; Muhammad Syafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the understanding of students' concepts and to know the difference in understanding of the concepts of class VIII students at SMPN 3 Pekanbaru with the application of the Teaching With Analogie (TWA) learning model and conventional learning on pressure material. This type of research is true experimental design with a posttest control only design. The research sample was the students class VIII of SMPN 3 Pekanbaru in academic year 2018/2019 which amounted to 43 students. The data of this study are data on students' understanding of concepts consisting of post-test scores through the application of TWA learning. Data were analyzed descriptively by looking at the percentage of conceptual understanding and inferentially analyzed using the T-test. Descriptive analysis results obtained, understanding the concept of experimental class students is higher than the understanding of the control class concept with an average score of conceptual understanding of experimental class students 73.69 including the moderate category and the concept of control class control scores 47.41 with very low categories . Based on the results of inferential analysis using the T-test , the significant value is 0,000 <0,05 so that it can be concluded that there is a significant difference between students' understanding of the concept after applying the TWA learning model and conventional learning.Key Words: TWA Model, Concept Understanding, Pressure